Perception of medical student about community medicine as subject in Government Medical College Bhavnagar, Western India - Trivedi, Bansi; Suthar, Nilkanth; Pandya, Shailen (International Journal Of Community Medicine And Public Health, 2023)
The primary goal of teaching community medicine (CM) to medical students is to educate them to practice as community and first-level physicians. Correct attitude and interest toward subject are necessary to gain knowledge and skill for future medical practice. Objectives were to explore the perception of medical students regarding knowledge of subject and willingness to take subjects as future carrier. The study was conducted during the march 2022 involving final year student and interns of government medical college Bhavnagar. Ten in depth interviews of study subjects were taken. Saturation of responses was achieved after eight interviews additional 2 interviews taken to confirm the saturation. All interviews were audio-recorded after obtaining written informed consent, transcribed and analyzed in form of codes and categories. Student perceive health promotion, Research, Health education, early detection of disease were main domains. They refuse to take CM subjects as their carrier. With a dream to become a famous and earning doctor, they do not want CM subject. There is need of clinical exposure and awareness regarding future scope of subjects among students. Future study can evaluate impact of such interventions on medial students.